The EU, ASEAN and Interregionalism Regionalism Support and Norm Diffusion between the EU and ASEAN - Allison, L. (The European Union in International Affairs,, 2015)
Using a framework of norm diffusion to determine the EU's international actorness in the context of its relations with ASEAN, this book provides a timely and in-depth analysis of EU-ASEAN relations. By investigating three aspects of regionalism support by the EU it presents a comprehensive account of norm diffusion between the EU and ASEAN.